PKM IMPLEMENTAION OF CATFISH CULTIVATION (BUDIKDAMBER) WITH PASSIVE CIRCULATION TECHNOLOGY AS AN EFFORT TO IMPROVE FOOD SECURITY IN ORPHANAGES, WARU, SIDOARJO - Rozi, Rozi; Aprilianita Sari, Luthfiana; Kismiyati, Kismiyati; Sekarjati, Cornelia; Roro Salma, Raden; Dharmansyah, Daud; Mutyara, Nanda; Yusufina, Dinda; Galang, Reksa; Manan, Addul (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Catfish (Clarias sp.) is a leading fishery commodity in Indonesia, prized for its taste and disease resistance, making it an ideal choice for farming even in areas with limited water and land. The Insanul Kamil Al-Khaer Orphanage in Sidoarjo, as a social foundation, faces challenges in providing productive and educational activities for its residents. Currently, the orphanage offers only worship and basic school activities for the children. To address this, the Community Service Program implemented a solution based on science and technology that would provide additional income, improve nutrition, and offer valuable learning experiences. The Community Service Program introduced the Budikdamber (fish farming in buckets) system, which is simple to set up and does not require extensive land or water. The program was implemented in three stages: preparing the materials, conducting socialization and training, and providing ongoing assistance in managing the catfish cultivation system using Budikdamber with passive circulation technology. After completing one full cycle of cultivation, the Community Service Program showed that the Budikdamber system improved food security, provided a steady income from surplus fish and vegetables, and reduced reliance on external donations. The program also highlighted the educational benefits for the children involved in managing the system. These results confirm the potential of the Budikdamber system to enhance community empowerment and sustainability. The Community Service Program provides a model for replication in other orphanages and community-based institutions. Further Community Service Programs are needed to evaluate the long-term impact and scalability of this innovative approach.